As interfaces do maravilhoso na obra Doze reis e a moça no labirinto do vento de Marina Colasanti - Cardoso, Gustavo Aragão (2023)
The present study is part of the literature studies and research of the post-graduation in languages of Universidade Federal de Sergipe, and it analyzes the marvelous that arises in Marina Colasanti's tales, noting the characteristics that they rescue from the traditional tales and to what extent they break with the classical structure promoting innovation. This qualitative research seeks to examine the interfaces of the marvelous, as well as the symbolic and compositional aspects of “Doze reis e a moça no labirinto do vento” and “Um desejo e dois irmãos”. Our hypothesis is that Marina Colasanti's tales are marvelous of faire nature which present certain regularity in terms of structural composition, however they innovate in terms of the proposed themes, promoting a parodic view of patriarchal society by reclaiming traditional narratives from a critical perspective and by highlighting female characters. The study is guided by this perspective, and it proposes the following questions: What are the interfaces of the marvelous that are manifested in Marina Colasanti's fairy tales? How do they take place in this literary work? Do the author's tales promote any kind of innovation in terms of language, narrative structure and thematic proposition when compared to traditional tales? Where are the ruptures and how do they are materialized in the narratives? These questions guide the development of the research analysis that do not intend to exhaust the understanding of the object of study, but it intends to contribute by encourage a critical and detailed view regarding the marvelous of the poetics of Marina Colasanti, taking into consideration a varied critical and theoretical references which is composed of: Colasanti (1982, 2015) Coelho (2020), Todorov (2017), Perdigão (1993), Propp (1984, 2002), Adam (2009, 2011), Genette (2018), Eliade (2013), Campbell (2007), Patai (1982), Mielietinski (1987, 2019), Gotlib (2006), Hutcheon (1991) among others.